2014
DOI: 10.1111/coep.12076
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance and Labor Force Participation: What Legal Recognition Does for Same‐sex Couples

Abstract: Using Current Population Survey data, I examine how same‐sex couples' labor force participation and health insurance coverage change as a result of their unions being legally recognized. The results indicate female same‐sex couples switch from arrangements where both members work to arrangements where only one member of the couple works. Being able to gain health insurance through a spouse's employer seems to play a major role in this change. Male same‐sex couples experience no change in their labor force part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 11 publications
2
20
2
Order By: Relevance
“…We consistently estimate that legal access to same-sex marriage did not systematically improve healthcare access and health-related outcomes for women in same-sex households. The null finding for women in same-sex households for health insurance contrasts with results from Buchmueller and Carpenter (2012) and Dillender (2015) who found that lesbians in same-sex relationships were significantly more likely to be insured when states extended marriage-like status to same-sex couples compared to the associated change for heterosexual women in different-sex relationships. Why might this be the case?…”
Section: Discussioncontrasting
confidence: 70%
“…We consistently estimate that legal access to same-sex marriage did not systematically improve healthcare access and health-related outcomes for women in same-sex households. The null finding for women in same-sex households for health insurance contrasts with results from Buchmueller and Carpenter (2012) and Dillender (2015) who found that lesbians in same-sex relationships were significantly more likely to be insured when states extended marriage-like status to same-sex couples compared to the associated change for heterosexual women in different-sex relationships. Why might this be the case?…”
Section: Discussioncontrasting
confidence: 70%
“…5 Syphilis is a sexually transmitted disease that is "relatively common among men who have sex with men" (Dee 2008(Dee :1056. The research perhaps closest to our study is that of Dillender (2015), who found that access to same-sex marriage reduced the labor market participation of lesbian couples, shifting these families from dual-to single-earner households-a change that Dillender attributed to access to partner's health insurance benefits.…”
Section: Introductionmentioning
confidence: 73%
“…However, it is at odds with Dillender's (2015) finding that access to legal marriage leads to more single-earner families among female same-sex couples. The explanations of the different findings may lie in institutional differences in the respective countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specialization gap between different-sex and same-sex couples tends to decrease over time (Giddings et al, 2014). Lesbian (but not gay male) couples shift from arrangements where both partners work into one-breadwinner arrangements after legal recognition of same-sex unions in the United States (Dillender, 2015). No significant impact of legal recognition of same-sex unions on their employment probabilities was found in California (Buchmueller & Carpenter, 2012).…”
Section: Effect Of Applicant's or Employee's Characteristicsmentioning
confidence: 99%